ANALISIS PENGUNGKAPAN GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY BERDASARKAN PEDOMAN UMUM GCG DAN STANDAR GRI G4 (Studi Kasus Pada PT Kaltim Prima Coal Tahun 2016) - Putri Husnah Aningtyas (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study is aimed to provide an overview of the disclosure of Good Corporate Governance and CorporateSocial Responsibility in the Sustainability report of PT. Kaltim Prima Coal in2016 based on the GeneralGuidelines for Governance Policy (KNKG 2006) and the GRI G4 standard. The type of research isqualitative research with a descriptive approach. In colleting data, this research uses the techniqueof literaturestudy and document study. Data analysis wa carried out by the descriptive and analysis method. The resultsof this study indicated that PT. Kaltim Prima Coal has implemented the principles of Good CorporateGovernance quite well according to KNKG guidelines. As for disclosure of Corporate Social Responsibility,PT. Kaltim Prima Coal has revealed existing indicators in accordance with GRI G4. However, the disclosureof each indicator by the companyha snot been quite detailed.Key words: Good Corporate Governance, Global Initiative Report (GRI), CorporateSocial Responsibility, Sustainability Report.